Ageing and the telomere connection: An intimate relationship with inflammation - Zhang, J.; Rane, G.; Dai, X.; Shanmugam, M.; Arfuso, Frank; Samy, R.; Lai, M.; Kappei, D.; Kumar, Alan Prem; Sethi, G. (2016)
© 2015 Elsevier B.V. Telomeres are the heterochromatic repeat regions at the ends of eukaryotic chromosomes, whose length is considered to be a determinant of biological ageing. Normal ageing itself is associated with telomere shortening. Here, critically short telomeres trigger senescence and eventually cell death. This shortening rate may be further increased by inflammation and oxidative stress and thus affect the ageing process. Apart from shortened or dysfunctional telomeres, cells undergoing senescence are also associated with hyperactivity of the transcription factor NF-?B and overexpression of inflammatory cytokines such as TNF-a, IL-6, and IFN-? in circulating macrophages. Interestingly, telomerase, a reverse transcriptase that elongates telomeres, is involved in modulating NF-?B activity. Furthermore, inflammation and oxidative stress are implicated as pre-disease mechanisms for chronic diseases of ageing such as neurodegenerative diseases, cardiovascular disease, and cancer. To date, inflammation and telomere shortening have mostly been studied individually in terms of ageing and the associated disease phenotype. However, the interdependent nature of the two demands a more synergistic approach in understanding the ageing process itself and for developing new therapeutic approaches. In this review, we aim to summarize the intricate association between the various inflammatory molecules and telomeres that together contribute to the ageing process and related diseases.